Dominant and Optional Components of Lexical Combinations in Russian Poetry - Pavlova, Larisa; Romanova, Irina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article reflects the experience of using the original software system “Hypertext Search for Companion-Words in Author’s Texts”, which allows one to find recurrent lexical combinations in the work of an author (the “corpus” direction of research) or in a thematically (by key lexical items) defined corpus of poems by various authors, right up to all Russian poetry (a “thematic” line of research). In the identified lexical combinations, a common lexical set is distinguished, due to the commonality of actual life or of language material, to common features of human perception, or to widespread associations. In this way a leitmotiv-based lexical environment emerges. It contains the dominant components of lexical combinations. Outside the leitmotiv set remain variations – lexemes that are occasionally added to the leitmotiv core in specific texts and thereby individualize those texts. These are optional components of combinations. Identifying the dominant and the optional components of lexical combinations is effective for comparing different authors and for establishing what they have in common and where they differ in their poetic interpretations of the same topic.